People’s Network for Land and Liberation (Commentary) - Melanie E. L. Bush (International Journal of Critical Diversity Studies)
In the context of end-stage capitalism, with intensifying global, economic, ecological, political and social crises this article discusses a formation in the United States that seeks to resist this trend, and imagine and build the new world centred on cooperative, regenerative and balanced systems. The People’s Network for Land and Liberation includes six organisations that have come together based on shared vision, values and program..